The association of emotion regulation problems in adults with the degree of autonomy and intimacy in their family of origin - Kreš, Barbara (Bogoslovni vestnik, 2025)
Family of origin factors have a major impact on individuals and the way they experience emotions and relationships in adulthood. In a study of 396 participants, who completed the “Family of Origin Scale” (FOS) and the “Difficulties in Emotion Regulation Scale” (DERS), we investigated the relationship between difficulties in emotion regulation in adulthood and the degree of autonomy and intimacy in the family of origin. The results show that higher levels of both traits in the family of origin were statistically significantly associated with better emotion regulation in adults. The results for each of the family of origin categories suggest, that clarity of expression, respect for others, and responsibility in the family of origin are the factors most strongly associated with better emotion regulation in participants. The study confirms the importance of promoting autonomy and intimacy in the family of origin for the emotional development of individuals and offers important starting points for therapeutic work with couples and families and for preventive activities in the field of pastoral work and mental health.
Keywords: autonomy; avtonomija; čustvena regulacija; duševno zdravje; emotion regulation; family of origin; intimacy; intimnost; izvorna družina; mental health; pastoral work; pastoralna dejavnost; psihoterapija; psychotherapy